Six-Year Training Improves Everyday Memory in Healthy Older People. Randomized Controlled Trial - Requena, Carmen; Turrero, Agustín; Ortiz, Tomás (Frontiers in Aging Neuroscience, 2016)
Purpose of the study. Everyday memory of older persons does not improve with intensive memory training programs. This study proposes a change in these programs based on a time-extended and massive intervention format. Design and Methods. The sample of 1007 healthy older persons (mean age 71.85; SD= 5.12) was randomized into 2 groups. The experimental group followed an extended 6 years of training (192 sessions over 192 weeks) whereas the control group received an intensive training (3 sessions per week for a total of 32 sessions in 11 weeks). The program included cognitive and emotional content whose effects were assessed with the Rivermead Behavioural Memory Test (RBMT) and with the Mini-Mental State Examination (MMSE). Both groups were evaluated initially, after 32 sessions, and again after 6 years. Results. The relative improvements measured with Blom’s derivative showed that everyday memory and mental status of the experimental group were significantly better both in the short (% 8.31 in RBMT and % 1.51 in MMSE) and in the long term (% 12.54 in RBMT and % 2.56 in MMSE). For everyday memory and mental level, the overall gain estimate representing the mean difference in pre-post change between time-extended and intensive groups was 0.27 (95 % CI: 0.13 - 0.40) and 0.54 (95 % CI: 0.40 - 0.67), respectively. Time-extended programs have significantly improved everyday memory in contrast with the usual intensive programs whose effects decay with time. There are also significant increases in mental level scores while daily life functionality is preserved in all subjects who completed the training. Implications. These results suggest that it is possible to preserve everyday memory in the long term with continuous training and practice. Massive and time-extended formats may contribute in the future to a paradigm shift in memory programs for healthy older people.